The Effect of Injury Prevention Training Programs on Anterior Cruciate Ligament Injuries in Team Sport Athletes - Bogardus, Rima L. (East Carolina University, 2013)
Objective: We sought to conduct a meta-analysis to determine whether neuromuscular training programs are effective at reducing anterior cruciate ligament (ACL) injuries. A secondary purpose was to identify and describe some common barriers to implementation for these training programs.  Data Sources: We used the keywords "anterior cruciate ligament," "injury," and "prevention" to conduct a search of Medline and the Cochrane library. A secondary search was conducted on article references lists.  Study Selection: Criteria for inclusion required that studies: 1) evaluate a neuromuscular training program for sports injury prevention, 2) report ACL injury as an outcome measure, 3) investigate team-sport athletes, 4) be prospective and include a control group, and 5) report the number of non-contact ACL injuries. Fifteen studies qualified for inclusion.  Data Extraction: The following data were utilized in the meta-analysis: Number of participants in the intervention group and control group, total number of ACL injuries in the intervention group and control group, and number of noncontact ACL injuries in the intervention group and control group.  Data Synthesis: Eight of the 15 identified studies reported non-contact ACL injuries separately from contact injuries and were included in the primary meta-analysis. We found that neuromuscular training programs were effective at reducing ACL injuries in the population evaluated (RR = 0.30 [95% CI 0.19 to 0.47]). Effectiveness of neuromuscular training programs was also indicated by a sensitivity analysis of all the studies (risk ratio = 0.41 [95% CI 0.27 to 0.63]) and only the randomized controlled trials (risk ratio = 0.52 [95% CI 0.34 to 0.80.])  Conclusions: Our meta-analysis showed that neuromuscular training programs are effective for preventing ACL injuries in team sport athletes. In addition, we identified five barriers to implementation of ACL injury prevention programs (i.e., motivation, time requirements, skill requirements for program facilitators, compliance, and cost), and provided suggestions to reduce these barriers.
Keywords: Public health; Health education; Health sciences; ACL; Injuries; Knee; Prevention; Sports injuries; Team sports; Accidents--Prevention; Anterior cruciate ligament